The Effect of Regional Taxes and Regional Levies on Regional Financial Independence which Impact Economic Growth - Zulfikar, Akbar Lufi; Swandari, Selly; Fitriah, Rinna Ramadhan Ain; Mahardika, Swadia Gandhi (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to determine the effect of regional taxes and regional levies on regional financial independence and their impact on economic growth in PPU. The method used is a quantitative approach with path analysis using SPSS software version 26. The results of the study indicate that regional taxes have a positive and significant effect on regional financial independence. The same thing is also shown by regional levies which significantly increase the level of fiscal independence. In addition, both regional taxes and regional levies have been shown to have a positive effect on economic growth in the region. Another important finding shows that regional financial independence also has a significant contribution to increasing economic growth. These results indicate that increasing regional original income from the tax and levy sector has a crucial role in strengthening regional fiscal capacity and encouraging sustainable economic development. Therefore, local governments need to continue to optimize the potential for revenue from taxes and levies through effective, transparent, and accountable governance in order to realize independent and prosperous regions.